Contribuições à análise de segurança de protocolos de criptografia quântica - Rios, Francisco Franklin Sousa (2018)
This thesis can be divided in three parts: I) Security analysis of quantum bit commitment (QBC). II) Quantum-chaotic key distribution (QCKD) using multiphoton pulses. III) Homodyne detection of weak coherent states. In respect to the security analysis of quantum bit commitment, it was shown that if one takes into account the spectral width of the light pulses and the frequency dependence of optical quantum gates, the QBC, contrary to what was previously considered, is not unconditionally insecure. In what concerns the QCKD, the usage of coherent states with continuous phase forces the eavesdropper to use an attack based on quantum homodyne tomography. In this case, it was shown that the transmitter can use coherent states with mean photon number much larger than the value traditionally used in quantum key distribution QKD, and the QCKD will still be secure. At last, in the homodyne detection part, an experiment was realized showing the detection, by an optical receiver based on PIN photodiode, of an analog modulating signal carried by a strongly attenuated coherent state.